THE CO-ADMINISTRATION OF POIL-2 WITH TGEV INACTIVATED VACCINE ENHANCES IMMUNE RESPONSE OF PIGLETS TO TGEV - H.Y. Yu; D.M. Gao; F.H. Li; D.P. Peng; B.B. Xia; Z.Y. He; W.J. Xu; H.Z. Li; J. Du; J. Zhao (Journal of Animal and Plant Sciences, 2024)
Porcine interleukin-2 (poIL-2) has not yet been demonstrated to be immune-enhancing against porcine transmissible gastroenteritis virus (TGEV) inactivated vaccine (IV), despite IL-2 having been proven to have immunological adjuvant effects for a variety of vaccinations. In this work, the impact of poIL-2 on TGEV IV in terms of immunological enhancement was investigated. Twenty four (24) SPF piglets were utilized and divided into six groups: PBS group, poIL-2 group, IV group, 10μg poIL-2+IV group, 50μg poIL-2 +IV group, and 250μg poIL-2+IV group. They received a second vaccine at 28 days point following the initial immunization. Serum and blood samples were obtained at various periods throughout the experiment. By using ELISA assay, neutralization assay, MTT assay, and flow cytometry assay, the TGEV-specific antibody expressions, neutralizing antibodies generations, interleukin-4 (IL-4), and interferon-gamma (IFN-γ) productions, peripheral blood mononuclear cells (PBMCs) proliferation response and lymphocyte phenotype subpopulations (CD3+, CD4+, and CD8+ immune cells) reflections were determined. The results showed that piglets inoculated with IV supplemented with poIL-2 significantly not only increased more piglet cellular immunity against TGEV by raising the degrees of IL-4, IFN-γ, Stimulation Index (SI), and the ratio of CD4+ /CD8+ cell subgroups, but also promoted more humoral immunity against TGEV by increasing levels of anti-TGEV specific antibodies and neutralizing antibodies (NAs) than those piglets inoculated with the TGEV IV alone. Additionally, the results suggested that porcine interleukin-2 (poIL-2) may improve pigs' immune responses in a dosage-dependent way.Our study revealed that poIL-2 had an immune-enhancing effect on the immunization of TGEV IV, and it possessed the potential to be applied as an immune-stimulating agent.
Keywords: Inactivated vaccine (IV); adjuvant; porcine transmissible gastroenteritis virus (TGEV); porcine interleukin-2 (poIL-2); immune response